BIO-TRACE ANALYSIS OF A BITE MARK SCAR LEFT ON THE HAND OF A PERPETRATOR OF A CRIME – A FORENSIC CASE REPORT - Atanas Christov; Teodora Kiryakova; Metodi Goshev; Biliana Mileva; Martin Angelov; Alexander Apostolov; Alexandar Alexandrov (Science & Research, 2019)

(untitled)
Introduction: We present a case of a homicide of a woman that was manually strangulated after she was sexually abused. On the right hand of the suspect specific scars were observed that could be dated around a month before our examination. In addition we were given gypsum casts of the deceased’s upper and lower jaws, as well as all the autopsy findings. Materials and methods: Examination of the suspect, analysis of the autopsy findings and the gypsum casts from the upper and lower jaws of the deceased, photo-superimposition, analysis of the results. Results: In this case, the obtained results showed the stable characteristics after the static and dynamic impact on perceptive surface (the hand of the perpetrator). These characteristics of the scars perfectly matched the specific features of the gypsum casts from the upper and lower jaw of the deceased. The study was performed by photo-superimposition and bio-trace analysis. Conclusion: Such types of forensic analysis are extremely important and informative in investigating criminal offenses, especially in cases where there is no other objective evidence (material evidence, testimony, available DNA research material, etc.) to identify the perpetrator of the crime.